Advancing the Mission: Highlights from the 2025 ASMA Conference - Marshall Magnusen (Journal of Applied Sports Management, 2025)
The Journal of Applied Sport Management (JASM) is the official publication of the Applied Sport Management Association (ASMA), which is a scholarly organization that builds research partnerships between faculty and students. ASMA also facilitates connections between sport management faculty and students studying sport and practitioners working in the sport industry. In 2025, the annual conference was hosted by the University of Cincinnati under the direction of Dr. Matt Huml. Highlights from the annual conference include Dr. Chad Seifried from Louisiana State University receiving the ASMA Distinguished Service and Mentorship Award and Dr. Lawrence Judge of Ball State University becoming an ASMA Research Fellow.
Keywords: economic impact; contingent employees; mentor; service; students; research